Gender and tourism sustainability - Eger, Claudia; Munar, Ana María; Hsu, Cathy H. C.
This book examines the relationship between gender and sustainability in tourism. Whilst an extensive body of work exists in the areas of gender and sustainability, these two fields of knowledge are seldom combined to examine tourism phenomena. When we look at the evolution of tourism, we see that sustainability has become an essential element in educational programmes, policy making and strategic considerations for organisations and destinations. Whilst the beginnings of tourism sustainability were challenging, presently, its relevance is seldom questioned. However, this situation is not the case with gender research. Although gender theorising and research have existed for over a century, and a rich legacy of knowledge exists on this topic, meaningful and respectful engagement with this line of scholarship is thus far peripheral in tourism studies. The aim of this book is to reflect on and rethink the intersection of gender and tourism sustainability through the lens of gender theory and feminist epistemology to stay with the trouble and devise pathways for sustainability gender knowledge. This book will be of great interest to students, researchers, and academics in tourism, gender and sustainability, as well as tourism management. The chapters in this book were originally published as a special issue of the Journal of Sustainable Tourism